2004
DOI: 10.1016/j.virol.2003.12.005
|View full text |Cite
|
Sign up to set email alerts
|

A naturally derived gastric cancer cell line shows latency I Epstein–Barr virus infection closely resembling EBV-associated gastric cancer

Abstract: In a process seeking out a good model cell line for Epstein-Barr virus (EBV)-associated gastric cancer, we found that one previously established gastric adenocarcinoma cell line is infected with type 1 EBV. This SNU-719 cell line from a Korean patient expressed cytokeratin without CD19 or CD21 expression. In SNU-719, EBNA1 and LMP2A were expressed, while LMP1 and EBNA2 were not. None of the tested lytic EBV proteins were detected in this cell line unless stimulated with phorbol ester. EBV infection was also sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
74
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 18 publications
3
74
1
Order By: Relevance
“…EBV-positive GC presents histologically and pathologically different features from EBV-negative GC (Akiba et al, 2008;Lee et al, 2004). EBV-positive GC exerts modulated latency 1, expressing latent genes such as EBNA1, LMP2A, BamHI-A rightward frame 1 (BARF1), and EBV-encoded RNAs (EBERs) (Imai et al, 1994;Oh et al, 2004). EBV lytic genes such as BamHI-Z leftward and rightward reading frame 1 (BZLF1 and BRLF1, respectively) are also expressed in EBVpositive GC following anti-cancer drug treatment (Feng et al, 2002;Jung et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…EBV-positive GC presents histologically and pathologically different features from EBV-negative GC (Akiba et al, 2008;Lee et al, 2004). EBV-positive GC exerts modulated latency 1, expressing latent genes such as EBNA1, LMP2A, BamHI-A rightward frame 1 (BARF1), and EBV-encoded RNAs (EBERs) (Imai et al, 1994;Oh et al, 2004). EBV lytic genes such as BamHI-Z leftward and rightward reading frame 1 (BZLF1 and BRLF1, respectively) are also expressed in EBVpositive GC following anti-cancer drug treatment (Feng et al, 2002;Jung et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…SNU-719 is a naturally derived EBV-infected GC cell line (24,25). AGS is an EBV-negative GC cell line (26) that was used to transduce the LMP2A gene from SNU-719 using a retroviral vector.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we reported that SNU-719 is a gastric carcinoma cell line that is naturally infected with EBV and that this cell line expresses EBNA-1, LMP2A and EBERs but not LMP1 similar to most EBVaGC cases (24). To examine the oncogenic potential of LMP2A in gastric epithelial cells, the LMP2A gene from SNU-719 was cloned and transduced into an EBV-negative gastric cancer cell line, AGS, using a retroviral vector and the growth ability of cell clones expressing LMP2A was analyzed.…”
Section: Introductionmentioning
confidence: 96%
“…23 In this study, we examined the effect of ionizing radiation on EBV genome expression in the SNU-719 cell line, a human gastric epithelial carcinoma cell line with natural EBV infection. 24 This cell line shows modified latency 1 EBV infection closely resembling EBVaGC and was reported to develop tumors when injected into nude mice and the developed tumor displayed similar characteristics with EBVaGC. 24,25 …”
mentioning
confidence: 90%
“…24 This cell line shows modified latency 1 EBV infection closely resembling EBVaGC and was reported to develop tumors when injected into nude mice and the developed tumor displayed similar characteristics with EBVaGC. 24,25 …”
mentioning
confidence: 90%